2012
DOI: 10.1111/pbi.12011
|View full text |Cite
|
Sign up to set email alerts
|

OsNAC5 overexpression enlarges root diameter in rice plants leading to enhanced drought tolerance and increased grain yield in the field

Abstract: SummaryDrought conditions are among the most serious challenges to crop production worldwide. Here, we report the results of field evaluations of transgenic rice plants overexpressing OsNAC5, under the control of either the root-specific (RCc3) or constitutive (GOS2) promoters. Field evaluations over three growing seasons revealed that the grain yield of the RCc3:OsNAC5 and GOS2: OsNAC5 plants were increased by 9%-23% and 9%-26% under normal conditions, respectively. Under drought conditions, however, RCc3:OsN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
244
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(278 citation statements)
references
References 89 publications
8
244
0
5
Order By: Relevance
“…Similar phenotypes have been reported in previous studies. Specifically, vigorous root radial growth was shown to be closely connected to high plant water potential under drought conditions in rice (Ekanayake et al, 1985;Price et al, 1997), and overexpression of OsNAC5, OsNAC9, and OsNAC10 promoted thicker radial root growth and enhanced drought resistance in rice (Jeong et al, , 2013Redillas et al, 2012). Interestingly, root aerenchyma were recently reported to improve drought tolerance by reducing root metabolic costs and optimizing root growth and water uptake from drying soil (Zhu et al, 2010;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenotypes have been reported in previous studies. Specifically, vigorous root radial growth was shown to be closely connected to high plant water potential under drought conditions in rice (Ekanayake et al, 1985;Price et al, 1997), and overexpression of OsNAC5, OsNAC9, and OsNAC10 promoted thicker radial root growth and enhanced drought resistance in rice (Jeong et al, , 2013Redillas et al, 2012). Interestingly, root aerenchyma were recently reported to improve drought tolerance by reducing root metabolic costs and optimizing root growth and water uptake from drying soil (Zhu et al, 2010;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that overexpression of droughtresponsive transcription factors can lead to enhanced drought resistance. For example, plants overexpressing Arabidopsis (Arabidopsis thaliana) AtMYB96 or HARDY (an AP2/ERF transcription factor) or transgenic rice (Oryza sativa) lines overexpressing OsAP37, OsNAC5, OsNAC9, OsNAC10, OsbZIP12, OsbZIP12, or OsbZIP23 all showed strong resistance to drought stress (Karaba et al, 2007;Oh et al, 2009;Jeong et al, 2010Jeong et al, , 2013Seo et al, 2011;Redillas et al, 2012;Joo et al, 2014;Park et al, 2015). Drought-responsive genes are often categorized into abscisic acid (ABA)-dependent or ABAindependent groups.…”
mentioning
confidence: 99%
“…QTL QPh9 governing PH, which was localised in 17141056-18060875 on chromosome 9 in TQ-ILs, was mapped together with OsbZIP72 encoding a zinc-finger TF, which was a positive regulator of ABA response and DT in rice ). QTL QPh11 governing PH located in 4572851-5558765 on chromosome 11 in LT-ILs was mapped together with OsNAC5 (Jeong et al 2013) encoding a NAC TF, which is expressed specifically in stamen and induced by drought and salt stresses. Allelism of the above DT QTLs identified in this study to the reported DT-related genes will need to be further clarified after fine mapping and cloning of the DT QTLs.…”
Section: Comparison Of Identified Dt Qtls With Dt-related Genes In Eamentioning
confidence: 99%
“…Nevertheless, several major DT QTLs, such as qDTY 12.1 (Bernier et al 2007;Mishra et al 2013), qDTY 1.1 (Vikram et al 2011), qDTY 6.1 (Venuprasad et al 2012), and the QTL closely associated with the markers EM11-11 ) and RM410 (Gu et al 2012) have been identified and used for developing DT varieties via MAS. Through functional and comparative genomic studies, many stressresponsive transcription factors were recently shown to affect DT (Liu et al 2007;Lu et al 2009;Ye et al2009;Zhao et al 2010;Jeong et al 2013). However, almost all related research studies on transcriptional factors have focussed only on testing of gene function, whereas few have reported on the successful use of those genes in breeding programs for stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of OsNAC6, OsNAC10, OsNAC9 and OsNAC5 in rice improved drought tolerance through increased root number and diameter (Lee et al, 2016a). Tolerance conferred by overexpression analysis was suggested to be mediated either by nicotianamine (NA) biosynthesis, glutathione relocation, or by incorporating and controlling factors involved in cell wall biosynthesis (Lee et al, 2016a, Lee et al, 2016b, Jeong et al, 2010, Redillas et al, 2012, Jeong et al, 2013. Transgenic rice plants overexpressing SNAC1 showed drought resistance both at the vegetative and reproductive stage by reducing water loss through regulation of stomatal opening possibly by regulating the expression of OsSRO1c but with no compromise in photosynthesis , Hu et al, 2006.…”
Section: Gene Discovery and Regulatory Mechanismsmentioning
confidence: 99%